1973
DOI: 10.1017/s0021859600058834
|View full text |Cite
|
Sign up to set email alerts
|

Stocking intensity and pastoral production: I. Changes in the soil and vegetation of a sown pasture grazed by sheep at different stocking rates

Abstract: A Phalaris tuberosa and Trifolium repens pasture was grazed continuously at stocking rates varying from 2-5 to 37-1 sheep per h a between 1964 and 1969. During this period herbage availability and composition, basal cover, root weight, water infiltration, soil moisture content, bulk density and chemical composition of the soil were measured at intervals.As stocking rate was increased, herbage availability, root weight, basal cover, soil pore space and the rate of water infiltration declined, and bulk density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…This relationship has been shown by Langlands and Bennett (1973), which found a positive correlation between soil bulk density and sheep density and a negative relationship between soil pore space and stocking density.…”
Section: Buffer Stripssupporting
confidence: 53%
“…This relationship has been shown by Langlands and Bennett (1973), which found a positive correlation between soil bulk density and sheep density and a negative relationship between soil pore space and stocking density.…”
Section: Buffer Stripssupporting
confidence: 53%
“…This impact is likely the result of increased stocking intensity decreasing the photosynthetic capacity of herbage and subsequent root development (Hart and Hoveland 1989). Langlands and Bennett (1973) observed that as stocking rate increases, nutrients located in the animal pool increase and those in the plant pool decrease. They found that as stocking rate increased, herbage availability, root weight, basal cover and soil pore space declined, but soil nutrient composition appeared to be unaffected by changes in stocking rate, especially in the surface soil.…”
Section: Microbial Biomassmentioning
confidence: 99%
“…Sharrow (1983) demonstrated that better nutrition is provided to animals in rotationally than continuously stocked paddocks, because amounts of plant biomass are greater. Grazing system and stocking intensity experiments in pasture research have focused on livestock weight gains, and forage quality and quantity (Langlands and Bennett 1973, Walton et al 1981, Jung et al 1985. However, the nutritional quality and quantity of forages in pasture also depend on the quality of the soil in which they grow.…”
mentioning
confidence: 99%
“…Previous research on the pasture feed year in this environment has been based on monoculture plot studies Robinson and Archer 1988), binary swards grazed by sheep (McPhee et al 1997;Ayres et al 2000), or mixed swards set stocked with sheep (Roe et al 1959;Langlands and Bennett 1973;Langlands and Holmes 1978). The significance of the present study is that it is the first description of the pattern of seasonal variation in herbage mass and nutritive value for mixed swards grazed by cattle in this environment.…”
Section: Discussionmentioning
confidence: 80%